GRANULAR CELL TUMOR SIMULATING BREAST CANCER ON SCREENING MAMMOGRAM: CASE REPORT - Negrão, Erika Marina Solla; Conz, Livia; Sabino, Silvia Maria Prioli de Souza; Watanabe, Anapaula Hidemi Uema; Picone, Jane Camargo da Silva Santos; Mauad, Edmundo Carvalho (Mastology, 2021)
Introduction: Granular cell tumor involving the breast parenchyma is very rare, representing between 5 and 15% of the presentations of this tumor. Due to the appearance of the image, it is confused with breast carcinoma; therefore, it can be a diagnostic challenge for medical mastologists, radiologists, and pathologists. Presentation of the case: We report the case of a 45-year-old woman who presented a lesion identified by ultrasound image with characteristics classified as highly suspected of malignancy (BIRADS 4c). The screening mammography detected a dense image of obscured margins, and the ultrasonography revealed a homogeneous irregular nodule with indistinct margins, located in the upper lateral quadrant of the right, posterior, and peripheral breast measuring 1.2 cm. The lesion was subjected to percutaneous biopsy, and the histological examination combined with an immunohistochemical study revealed that it was a granular cell tumor. Conclusion: Although the granular cell tumor of the breast is a rare breast cancer, it must be considered in the differential diagnosis of lesions detected in imaging examinations. The granular cell tumor of the breast is a benign lesion, but the radiological findings suggest a malignant tumor, clinically and radiographically impossible to establish a definitive diagnosis without a biopsy.